2021
DOI: 10.21608/ejchem.2021.104296.4838
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles using Egyptian Propolis Extract and its Antimicrobial Activity

Abstract: There is great research interest in synthesizing nanomaterials using environmentally friendly methods due to the many applications of these materials in several fields. In this paper, a facile and green chemistry method was used to synthesize silver nanoparticles (AgNPs) using the Egyptian propolis as reducing and capping agent. Different parameters such as aqueous propolis extract quantity, pH, reaction time, and temperature were investigated to get the optimal conditions for synthesis of AgNPs. When aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…For the biosynthesis of silver nanoparticles, this wavelength value of maximum absorption is consistent with the values measured in previous studies [53]. It depends on the concentrations of silver salt and the functional groups in the plant used in the reaction [54][55][56].…”
Section: Uv-spectroscopy Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…For the biosynthesis of silver nanoparticles, this wavelength value of maximum absorption is consistent with the values measured in previous studies [53]. It depends on the concentrations of silver salt and the functional groups in the plant used in the reaction [54][55][56].…”
Section: Uv-spectroscopy Analysissupporting
confidence: 90%
“…The best absorption is for sample p3, pH = 7.5, and this means the probability of silver nanoparticle formation increases in the neutral reaction medium. As well as the absorption peak, which is related to the size and shape of the formed Ag-NPs, the role of the pH factor is to increase and alter the electrical charges of biomolecules, which in turn affect the capping, stability, and growth of Ag-NPs [56,60]. This study demonstrated that the…”
Section: The Ph Factormentioning
confidence: 96%
“…The appearance of the brown color was an indication of formation of colloidal silver particles in the medium (Lotfy et al 2021 andMohamed et al 2022). The increase in color intensity may be because of increasing number of synthesized nanoparticles by reduction of silver ions present in the aqueous solution.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the synthesized AgNPs aggregates were agglomerated because of the phenomenon of coagulation of the smaller particles of AgNPs [40]. Another explanation is that DLS measures the hydrodynamic radius of silver particles loaded by the bio-organic material on its surface, so the high intensity of the scattered light measured the larger (false) size of AgNPs, unlike TEM, which showed the actual size [41].…”
Section: Discussionmentioning
confidence: 99%